Peran Guru dalam Menerapkan Pembelajaran Sosial Emosional untuk Mewujudkan Sekolah yang Ramah dan Empatik - Indah Khairani (Jurnal Pendidikan Tuntas, 2025)
Social Emotional Learning (SEL) has become an essential approach in modern education as it focuses on the development of students’ social and emotional competencies, such as self- awareness, empathy, and the ability to build positive relationships. This article aims to examine the strategic role of teachers in implementing SEL as an effort to create a friendly and empathetic school environment. Using a descriptive-qualitative approach, this article explores various strategies employed by teachers to integrate SEL into the learning process, the challenges they face, and its impact on school climate. The discussion reveals that teachers play a central role as facilitators, role models, and motivators in shaping a school culture that supports students’ character development. Consistent implementation of SEL contributes to reducing social conflicts, enhancing students’ emotional well-being, and creating an inclusive and supportive learning atmosphere. Therefore, teacher training, policy support, and collaboration among school members are key factors in the success of this program.